2016
DOI: 10.3389/fcvm.2015.00039
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Coronary Artery Bypass Surgery: Ready for Prime Time and Outcome Prediction?

Abstract: Coronary artery bypass surgery (CABG) is still one of the most frequently performed surgical procedures all over the world. The results of this procedure have been constantly improved over the years with low perioperative mortality rates, with relatively low complication rates. To further improve these outstanding results, the clinicians focused their attention at biomarkers as outcome predictors. Although biological testing for disease prediction has already been discussed many times, the role of biomarkers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Samples were collected before and after bypass surgery from a cohort of 20 patients. As we 21 and others 22 have shown, cardiopulmonary bypass, by virtue of the invasive nature of the surgery and the requirement for bypass intervention, invariably results in some degree of ‘systemic inflammation’. In this cohort 18 of the patients developed clinically relevant SIRS (see Supplementary Table 2 ), of which for one patient (patient 1; see Supplementary Table 2 ) an incomplete sample range was obtained.…”
Section: Resultsmentioning
confidence: 82%
“…Samples were collected before and after bypass surgery from a cohort of 20 patients. As we 21 and others 22 have shown, cardiopulmonary bypass, by virtue of the invasive nature of the surgery and the requirement for bypass intervention, invariably results in some degree of ‘systemic inflammation’. In this cohort 18 of the patients developed clinically relevant SIRS (see Supplementary Table 2 ), of which for one patient (patient 1; see Supplementary Table 2 ) an incomplete sample range was obtained.…”
Section: Resultsmentioning
confidence: 82%
“…Perioperative myocardial injury has been thought as a kind of serious complication for CABG, which is also related to a high level of morbidity and mortality during a long period (13). Under the circumstance that no effective pharmacological therapy can be used to treat the perioperative myocardial, but early preventive measures, like pre-OP risk predication and perioperative optimization, could be a good choice in reducing the myocardial injury to some degree (14). What's more, due to a novel biomarker, myocardial injury prediction is of great use in providing the valuable information in the management during the perioperative period (15).…”
Section: Discussionmentioning
confidence: 99%
“…Togan et al7 recently reported that preoperative elevation of ESR is a risk factor for the postcoronary artery bypass graft (post-CABG) complication in male patients. Similarly, Parolari et al12 stated that increased levels of other similar biomarkers such as IL-1 and CRP are associated with the unfavorable outcome following CABG. The primary purpose of the present study was to investigate the relationship between elevated levels of preoperative ESR and short- and mid-term outcome and postoperative complications in adult heart operations.…”
Section: Introductionmentioning
confidence: 95%